Mappin g the Intellectual Landscape of TEFL Methodology: A Bibliometric Analysis (VOSviewer) of Global Trends, Thematic Clusters, and Researcher Collaborations Based on Scopus Data (2015–2025) - Zakia Fikliona; Fauzan Abdurrahman; Riska Prasanti; Pefiya Nurlita; M Fathan Audzan Ferhend (Kilau Publishing, 2025)
This study maps the intellectual landscape of Teaching English as a Foreign Language (TEFL) methodology research from 2015 to 2025 using a bibliometric approach supported by VOSviewer visualization. The analysis draws data from Scopus-indexed publications and examines annual research trends, geographic and institutional contributions, thematic clusters, and collaborative networks. The findings indicate a substantial increase in TEFL methodological research during the period, with a sharp rise between 2023 and 2024 due to the global expansion of digital learning environments. Countries such as the United States, China, the United Kingdom, and Australia dominate research output, while Asian regions show rapid growth supported by international partnerships. Keyword co-occurrence analysis reveals four major clusters: communicative pedagogy, technology integration, adaptive and flipped learning, and assessment. Temporal analysis highlights a shift from communicative approaches in early years toward technology-driven pedagogies, adaptive models, and AI-supported assessment practices in later years. The study provides an integrated understanding of TEFL methodology development, offering insights to guide future research agendas in English language education